Missing images: autobiographical memory in Aphantasia and blindness - McCormick, Cornelia; Lange, Sven (Frontiers in Cognition, 2025)
Mental visual imagery, especially the ability to construct naturalistic scenes seems central to vivid episodic autobiographical memory (AM). This mini review will first highlight the neural anatomy of different aspects of mental imagery, focusing on the roles of the hippocampus, ventromedial prefrontal cortex and posterior neocortex and the consequences of damage to these regions to AM. We will then contrast the consequences of missing images for AM in two special populations with no apparent brain damage: Congenital Aphantasia (i.e., lack of visual imagery) and congenital blindness (i.e., lack of visual perception). We propose that Aphantasia leads to impaired scene construction and reduced AM reliving. Despite limited evidence on AM in congenitally blind individuals, they seem to rely on auditory and tactile information to construct (scene) imagery, which in turn may support vivid AM reliving. The main findings here suggest that mental scene imagery, rather than visual encoding, is crucial for AM. This conclusion has far-reaching implications for understanding memory disorders, mental health, and a call to protect our imagination.